Respuesta :

Answer:

Equations 2 and 3 are correct

Answer:

Option 2 and 3

Step-by-step explanation:

We know that as per distributive law, we have [tex]a(b+c)=ab+ac[/tex].

Option 1.

[tex]-5x^3(3x^3+2)=-15x^6-10x^3\neq -15x^9-10x^3[/tex]

So, option 1 is not correct.

Option 2.

[tex]-2c^6(5c^3+6)=-10c^9-12c^6[/tex]

So, option 2 is correct.

Option 3.

[tex]-3y^5(2y^3+3)=-6y^8-9y^5[/tex]

So, option 3 is correct.

Option 4.

[tex]-4b^4(5b^2+6)=-20b^6-24b^4\neq -20b^8-24b^3[/tex]

So, option 4 is not correct.

ACCESS MORE